A Wideband, Wide Scanning Tightly Coupled Dipole Array With Integrated Balun (TCDA-IB) - Doane, Jonathan P.; Sertel, Kubilay; Volakis, John L. (IEEE transactions on antennas and propagation, 2013)
A key challenge in the design of wideband dipole phased arrays is the design of equally wideband baluns which are sufficiently compact to fit within the unit cell (typically in the linear dimension at low frequencies). In this paper, we exploit the reactance of a compact Marchand balun as an impedance matching network for each array element. The elimination of bulky external baluns results in a significant reduction of size, weight and cost, while the bandwidth is simultaneously improved by over 30%, compared to standard feeding techniques. In this manner, a tightly coupled dipole array with an integrated balun (TCDA-IB) is developed which achieves 7.35:1 bandwidth (0.68 - 5.0 GHz) while scanning to ±45° in all directions, subject to . In a dual-polarization configuration, the TCDA-IB has low cross polarization of over the majority of the band. Measured results are presented for a prototype 8 × 8 element TCDA-IB, showing good agreement with simulation.